A Poly-vinyl Alcohol (PVA)-based phantom and training tool for use in simulated Transrectal Ultrasound (TRUS) guided prostate needle biopsy procedures. (October 2021) - Gautam, Umesh C; Pydi, Yeswanth S; Selladurai, Sathiyamoorthy; Das, Chandan J; Thittai, Arun K; Roy, Sitikantha; Datla, Naresh V
Highlights: A tissue mimicking phantom has been developed for use as training tool in simulated TRUS guided prostate biopsy procedures. The phantom is made of a Poly-vinyl Alcohol (PVA) material, the stiffness of which is tunable, and which is durable and compatible with ultrasound. The stiffness and shrinkage of the PVA material varies with its concentration and the number of freeze-thaw cycles. The acoustic properties of the prostate phantom are close to those of the actual human prostate. Abstract: Trans-rectal ultrasound-guided needle biopsy is a well-established diagnosis technique for prostate cancer. To enhance the needle manoeuvring skills under ultrasound (US) guidance, it is preferable to train medical practitioners in needle biopsy on tissue-mimicking phantoms. This phantom should mimic the morphology as well as mechanical and acoustic properties of the human male pelvic region to provide a surgical experience and feedback. In this study, polyvinyl alcohol (PVA) was used and evaluated for prostate phantom development, that is stiffness tunable, US-compatible and durable phantom material. Three samples, each with 5%, 10%, and 15% concentration of PVA material, were prepared, and their mechanical and shrinkage characteristics were investigated. The anatomy of male pelvic region was used to develop an anatomically correct phantom. Later US-guided needle biopsy was performed on the phantom. The range of elastic moduli of the PVA samples was 2∼146 kPa. Their elastic moduli and volumes were found to remain statistically close from seventh to eighth freeze-thaw cycle ( p >0.05). Initial US scans of the phantom resulted in satisfactory B-mode images, with a clear distinction between the prostate and its surrounding organs. This study demonstrated the applicability of PVA hydrogel as a phantom material for training in US-guided needle biopsy.